Effect of step up exercise on cognitive attention with stroop test in Bengali male college students - Debray, Parthasarathi; Biswas, Susanta; Biswas, Prasanta; Saha, Tapasi; Pal, Madhu Sudan (Asian Journal of Medical Sciences, 2015)
Introduction: A beneficial influence of exercise on cognitive and brain functions has been established. Exercise is drawing increasing research attention for improving neurocognitive functions. Aims: The aim of the present study is to examine the effect of step up exercise on mental attention with strop test in Bengali male college students. Methodology: Twenty eight (28) apparently healthy male sedentary college students from the same socio-economic background, having mean age of 22.4 ± 1.02 years, body height of 165.3 ± 6.34 cm and body weight of 55.5 ± 9.01 kg were recruited for the present study on the basis of random sampling from the undergraduate students of the NS Mahavidyalaya of Tripura. A computer based modified ‘Stroop color word’ test based on the original Stroop test (Stroop, 1935) to identify cognitive performance. After completion of stroop test in resting sitting condition participants were asked to complete Queen College Step Test to measure VO2 max. After completion of 3 mins step up exercise a recovery time of 5-15 seconds were taken for VO2 measurement and immediately after taking recovery pulse participants were asked to perform stroop III subtask to see the effect of exercise on the cognitive performance of the college students of Tripura. Results: The mean VO2 max to be found 49.1 ± 6.25 ml.kg-1.min-1. The mean time to complete Stroop sub task Tasks III was found 194.3 (±46.34) sec. After 3 minutes step-up exercise it has been shown that the mean stroop III score was improved from 194.3 (±46.34) to 160.4 (± 31.42) sec. Conclusion: It is observed in the present study that the speed of performance (i.e., stoop tasks) is improved after short term moderate exercise. DOI: http://dx.doi.org/10.3126/ajms.v6i6.12602 Asian Journal of Medical Sciences Vol.6(6) 2015 66-69